Unraveling Potential Tauopathy Biomarkers in Cerebrospinal Fluid: Insights from Olfactory Tract Data - Lachén-Montes, Mercedes; Cartas-Cejudo, Paz; Anaya-Cubero, Elena; Cortés, Adriana; Fernández-Irigoyen, Joaquín; Santamaría, Enrique (Methods in molecular biology (Clifton, N.J.), 2025)
Due to the increase in life expectancy, the prevalence of neurodegenerative diseases is estimated to grow considerably in the next decades. Unfortunately, there are no current curative treatments for the majority of these disorders and this might be due to the lack of early diagnosis. Nowadays, diagnosis of neurodegenerative disorders is mainly based on neuroimaging and clinical symptoms, although postmortem neuropathologic confirmation remains the gold-standard diagnostic technique. In this sense, cerebrospinal fluid (CSF) proteome is considered a valuable molecular repository for diagnosing and targeting the neurodegenerative process. On the other hand, olfactory dysfunction is an early symptom that affects Alzheimer's disease (AD) and other tauopathies' patients. That is why we consider that the application of tissue proteomics in primary olfactory structures is an ideal approach to explore early pathophysiological changes, detecting olfactory proteins that might be tested in CSF as potential biomarkers. In this chapter, we have applied peptide fractionation methods followed by tandem mass spectrometry (nanoLC-MS/MS), in silico analysis and semi-quantitative orthogonal techniques in the olfactory tract derived from AD subjects. After obtaining the differential OT proteome, we suggest that the use of different bioinformatic workflows might be a valuable workflow to discover potential disease biomarkers for AD and other tauopathies.